A spatial-based explanation for institutional trust in Georgia: Evidence from the maternal healthcare system. Issue 1 (January 2022) - Badashvili, Medea; Byelousova, Anastasiya; Gupta, Parth; Liu, Amy H; Pizzi, Elise; Sanchez, Michael; Shengelia, Lela; Unapkoshvili, Mariana; Wang, Lyndsey; Wierschke, Katherina
When an institution is not easily accessible—for example, it is geographically far—it can be hard for institutional trust to develop. The institution is not only unavailable, but it can also be seen as inappropriate, non-affordable, unapproachable, and unacceptable. In this paper, we examine whether reducing distance to medical facilities and professionals can improve trust in the maternal healthcare system. We do so by focusing on developments in Georgia. Since 2013, the government has aggressively closed the distance to service access not by building more facilities or hiring more staff per se, but by upgrading and funding existing facilities and professionals in a national network to better coordinate service provisions at the local levels. Employing an original survey, we match GPS coordinates to measure distance and use regression analysis to demonstrate how ensuring every woman has access to maternal healthcare at the right place at the right time has improved institutional trust in the system. The implications highlight results that are generalizable beyond both the country and maternal healthcare.